Pembinaan sistem data logging untuk alat penerima GPS satelit satu frekuensi - Mardina Abdullah,; Ahmad Faizal Mohd Zain,; Norbahiah Misran,; Andrew Ong Yee Jack, (2007)
This paper describes the development of logging and transferring data system using a single frequency GPS receiver. GPS is a constellation of 24 satellites launced by the United States to broadcast navigation information such speed, time and location of a receiver. A software has been developed to collect dan save data using a ﬁling format and to transfer ﬁles automatically to a local area via a modem communication in which it is also tested using a RS232 serial communication link. The software can receive and save ﬁles with error correction method. It also has a capability to transmit the navigation information in every three minutes from a GPS receiver which is located in a far or remote area to a local area. So that the informations can be used for geodesy and geoinformation purposes, and also for scientiﬁc research such as radio propagation and, ionospheric total electron content measurement and others. The existence of this datalogging system which can also be displayed on a website, helps users to easily obtain the latest informations with high reliability